2022
DOI: 10.1038/s41398-022-02201-8
|View full text |Cite
|
Sign up to set email alerts
|

Neural substrates of reward anticipation and outcome in schizophrenia: a meta-analysis of fMRI findings in the monetary incentive delay task

Abstract: Dysfunction of the mesocorticolimbic dopaminergic reward system is a core feature of schizophrenia (SZ), yet its precise contributions to different stages of reward processing and their relevance to disease symptomology are not fully understood. We performed a coordinate-based meta-analysis, using the monetary incentive delay task, to identify which brain regions are implicated in different reward phases in functional magnetic resonance imaging in SZ. A total of 17 studies (368 SZ and 428 controls) were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 124 publications
3
10
2
Order By: Relevance
“…These neurodevelopmental alterations are associated with increased neuronal excitation, reduced inhibitory neural activities, and the resultant impulsive behaviors 101 . In line with our findings, previous research has shown a correlation between higher psychotic risk and neuroanatomical alterations in the right temporal fusiform, right temporal pole, and right parahippocampal gyrus 93 , as well as greater neural activations in limbic regions such as the insula and cingulate cortices during reward outcomes in MID task 102 . Overall, our findings on the heterogeneous effects of neighborhood deprivation contribute to the growing body of literature showing the role of glucocorticoid and reward systems in modulating the adverse effects of environmental deprivation on psychosis 92,94,96,103,104 .…”
Section: Discussionsupporting
confidence: 93%
“…These neurodevelopmental alterations are associated with increased neuronal excitation, reduced inhibitory neural activities, and the resultant impulsive behaviors 101 . In line with our findings, previous research has shown a correlation between higher psychotic risk and neuroanatomical alterations in the right temporal fusiform, right temporal pole, and right parahippocampal gyrus 93 , as well as greater neural activations in limbic regions such as the insula and cingulate cortices during reward outcomes in MID task 102 . Overall, our findings on the heterogeneous effects of neighborhood deprivation contribute to the growing body of literature showing the role of glucocorticoid and reward systems in modulating the adverse effects of environmental deprivation on psychosis 92,94,96,103,104 .…”
Section: Discussionsupporting
confidence: 93%
“…Thus, decreased striatal activation was consistently found in individuals with high CAPE scores [ 77 , 84 ] and those with high negative schizotypy [ 81 ] during reward anticipation. During reward consummation, decreased amygdala activation was found in negative schizotypal individuals [ 81 ] in line with findings in schizophrenia patients [ 139 ]. On the other hand, the hyperactivation of VLPFC in high positive schizotypy individuals during reward anticipation [ 81 ] again implicates compensatory mechanisms in subclinical individuals.…”
Section: Discussionsupporting
confidence: 75%
“…Focusing on common and distinct dysfunctional patterns of brain activation between CHR groups and SZ groups is of great significance to delineate neurobiological characteristics in different stages of psychosis. Although we did not make a direct comparison of SZ and CHR individuals in the current meta-analysis, compared with the results of recent meta-analyses focusing on SZ, we found that SZ and CHR individuals showed similar brain hypoactivation patterns in the mesolimbic circuit but different activation profiles in the PFC/ACC during reward anticipation ( Leroy et al, 2020 ; Zeng et al, 2022 ). Importantly, SZ exhibited reduced anticipation-related activity in both ventral and dorsal striatal regions ( Zeng et al, 2022 ), whereas the CHR group showed reduced activation only in the DS region.…”
Section: Discussioncontrasting
confidence: 66%
“…Although we did not make a direct comparison of SZ and CHR individuals in the current meta-analysis, compared with the results of recent meta-analyses focusing on SZ, we found that SZ and CHR individuals showed similar brain hypoactivation patterns in the mesolimbic circuit but different activation profiles in the PFC/ACC during reward anticipation ( Leroy et al, 2020 ; Zeng et al, 2022 ). Importantly, SZ exhibited reduced anticipation-related activity in both ventral and dorsal striatal regions ( Zeng et al, 2022 ), whereas the CHR group showed reduced activation only in the DS region. Hypoactivation in the dorsal and VS during the anticipation of monetary incentives was also observed in first-episode SZ patients ( Schlagenhauf et al, 2009 ; Esslinger et al, 2012 ; Nielsen et al, 2012 ; Hanssen et al, 2015 ), chronic SZ patients (Juckel, et al, 2006a , 2006b ), and their unaffected first-degree relatives ( Grimm et al, 2014 ; de Leeuw et al, 2015 ).…”
Section: Discussioncontrasting
confidence: 66%